The Woke Debate in Academia— What Could Take Us Further? - Stolker, Carel (International Higher Education, 2022)
The current woke debate has the potential to cause a rift in our university communities. What can we do to avoid that, and how can we make sure that the debate makes us stronger as a community, instead of weaker? This article presents a few suggestions from a former university president.